Computational study of synthetic and natural polymer additives — Antioxidant potential of BHA, TBHQ, BHT, and curcumin - Dalal K. Thbayh; Bela Fiser; Fiser Béla; Фішер Бейло (Elsevier, 2022)
Abstract. The antioxidant potential of commonly used synthetic and natural antioxidant additives, including butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), tert‑butylhydroquinone (TBHQ), and natural additive, curcumin have been studied and compared by calculating the bond dissociation enthalpy (BDE), ionization potential (IP), proton dissociation enthalpy (PDE), proton affinity (PA), and electron transfer enthalpy (ETE) values for each potential hydrogen donor site. The results indicate that, in each additive an Osingle bondH group has the highest antioxidant potential (lowest BDE value). The studied molecules can be ranked based on their antioxidant potential as follows: BHT > BHA ≈ TBHQ > curcumin A > curcumin D. By comparing with commonly used polymers, in each studied species, there is at least one X-H bond which has a lower BDE value than in the corresponding polymeric material. Thus, all studied additives are potentially applicable to protect polymeric materials. BHT is the best radical scavenger additive in case of the hydrogen atom transfer (HAT), and the sequential proton loss electron transfer (SPLET) mechanisms to donate a H atom, but in single electron transfer proton transfer (SETPT) curcumin could also be suitable.
Editorial board: https://www.sciencedirect.com/journal/polymer-degradation-and-stability/about/editorial-board
Contents: https://www.sciencedirect.com/journal/polymer-degradation-and-stability/vol/201/suppl/C
Keywords: DFT; Phenolic compounds; Antioxidant mechanism; HAT; SETPT; SPLET